Increasing Exposure of Digital Devices and Its Impact on Physiological and Psychological Development Among Children: A Systematic Review of Prospective Studies - Pandey, Saroj R.; Vaishnav, Rajshree S. (International Journal of Membrane Science and Technology, 2023)
It is true that technology make our lives very comfortable, but it should not be at the expense of our health. Exposure to radio frequency electromagnetic fields has raised scientific and public concerns. It is necessary to acknowledge the adverse effects on the health among children using digital devices. Innovation in computers and mobile 5G phones, online games and use of social media applications are in a great boom. Study of various reviews give the current exposure effects due to these radiations. Here in this paper, we have included studies published in peer-reviewed journals between 2010 and 2023 which are based on empirical evidence and reviews. We have identified 57 published papers on health effects of digital devices on physiological and psychological aspects of children. Some of the major health related physiological problems are reported in the reviews are musculoskeletal problems, sleep disturbances, headache issues and eyestrain. Whereas Psychological problems highlighted in the reviews are poor concentration, memory loss, stress, depression etc. At present, there is insufficient data to draw firm conclusions about health effects due to the exposure of digital devices which are occurring in the everyday environment. Currently, there is little epidemiological evidence indicating that the use of digital devices causes adverse health effects.